The IHS-FTR Transformations Based Image Fusion Algorithm For Remote Sensing Images - Manchanda, Meenu; Gambhir, Deepak (International Journal of Computer Sciences and Engineering, 2025)
Image fusion has been attracting researchers with the aim of finding solutions to a wide area of applications. In the area of remote sensing, the increasing availability of imaging sensors, operating in a variety of spectral bands, definitely provides strong motivations. Because of the trade-off observed between sensors with a high spatial resolution with only a few spectral bands and sensors with low spatial resolution having many spectral bands, spatial enhancement of poor-resolution image and vice-versa is desirable. Thus, a new method of fusing different resolution images based on IHS transform and fuzzy transform (FTR) is proposed. The main aim is to produce a fused image with high spatial as well as high spectral resolution by fusing two images, an Ms image and a Pan image, the former with high spectral resolution but poor spatial resolution and the latter with high spatial resolution but poor spectral resolution. Experimental results obtained from the fusion of different pairs of input images prove the effectiveness of the proposed algorithm